Factors Affecting the Management of Pesticide Business: The Case Vietnam - Thanh, Ngo Chi; Phuong, Le Thi; Cuong, Le Van (Asian Journal of Agriculture and Rural Development, 2020)
Based on the context of Thanh Hoa province, Vietnam, this paper studies the factor affecting the management of pesticide business for the case of Vietnam. The authors propose the model with five factors affecting the management of pesticide business activities in Thanh Hoa province, including (i) Content and implementation methods of the legal documents; (ii) Capacity of the management staff; (iii). Awareness and legal compliance of the pesticide traders; (iv) Budget, infrastructure, and facilities for the pesticide management; and (v) Collaboration between management stakeholders. In this study, 176 pesticide traders were investigated for the 5 mentioned factors in Thanh Hoa province. The question of factors influencing the management of pesticide business activities in the province was done by using Exploratory Factor Analysis and Regression Analysis. The result showed that all the above factors have affected the management of pesticide business in which, the collaboration between the management stakeholders and the awareness and legal compliance of pesticide traders are the most affected while the content and implementation methods of the legal documents are less influence. Based on these results, the paper proposes solutions to improve the management of pesticide trading activities in the coming time in Thanh Hoa province.